A COMPARATIVE ANALYSIS OF MODERN VULNERABILITY SYSTEMS AND DATABASES: A COMPARATIVE ANALYSIS OF MODERN VULNERABILITY SYSTEMS AND DATABASES - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This scientific article examines and compares several modern vulnerability management systems and databases, such as CVE, CWE, EUVD, NVD, and OSVDB. The goal is to understand how these resources differ in scope, structure, and interoperability. In the article of the analysis, particular attention is paid to platforms like MITRE’s frameworks, Exploit-DB, and Rapid7-DB, as well as to international initiatives such as Japan’s JVN project. The scientific study also reviews the scoring models they employ, mainly CVSS, and considers alternatives like VEDAS. Overall, the results highlight how each system contributes differently to strengthening cybersecurity practices and how they can complement one another in real-world defense strategies.